A survey of theological seminary libraries belonging to Asia Graduate School of Theology (AGST) with implications for resource sharing - Rodriguez, Elizabeth V. (Institute of Library Science, University of the Philippines Diliman, 1990)
This study is a descriptive survey of the status and prospects of resource sharing activities among the theological seminary libraries belonging to Asia Graduate School of Theology.The survey was conducted using the descriptive research method employing the questionnaire and interviews in gathering data. Documents like reports, handbooks, brochures, catalog and other materials pertaining to the seminaries were also examined to supplement and refine the data where first hand information was not available.